Safe and Effective Anterior Ankle Arthroscopy with A 2-mm Diameter Operative System. Issue 1 (January 2022) - Stornebrink, Tobias; Altink, Nienke; Appelt, Daniel; Wijdicks, Coen A.; Stufkens, Sjoerd A.; Kerkhoffs, Gino
Category: Ankle; Arthroscopy; Basic Sciences/Biologics Introduction/Purpose: The purpose of this study was to assess whether all significant structures in the ankle could be visualized and surgically reached during 2-mm diameter operative arthroscopy, without inflicting iatrogenic damage. Methods: A novel, 2-mm diameter arthroscopic system was used to perform a protocolled arthroscopic procedure in 10 fresh- frozen, human donor ankles. Standard anteromedial and anterolateral portals were utilized. Visualization and reach with tailored arthroscopic instruments of a protocolled list of articular structures were recorded and documented. A line was etched on the most posterior border of the talar and tibial cartilage that was safely reachable. The specimens were dissected and distances between portal tracts and neurovascular structures were measured. The articular surfaces of talus and tibia were photographed and inspected for iatrogenic damage. The reachable area on the articular surface was calculated and analysed. Results: All significant structures were successfully visualized and reached in all specimens. The anteromedial portal was not in contact with neurovascular structures in any specimen. The anterolateral portal collided with a branch of the superficial peroneal nerve in one case, but did not cause macroscopically apparent harm. On average, 96% and 85% of the talar and tibial surfaces was reachable respectively, without causing iatrogenic damage. Conclusion: 2-mm diameter operative arthroscopy provides safe and effective visualization and surgical reach of the anterior ankle joint. It may hold the potential to make ankle arthroscopy less invasive and more accessible.